2012
DOI: 10.1016/s1995-7645(12)60084-4
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis: Current status of available drugs and new potential drug targets

Abstract: The control of Leishmania infection relies primarily on chemotherapy till date. Resistance to pentavalent antimonials, which have been the recommended drugs to treat cutaneous and visceral leishmaniasis, is now widespread in Indian subcontinents. New drug formulations like amphotericin B, its lipid formulations, and miltefosine have shown great efficacy to treat leishmaniasis but their high cost and therapeutic complications limit their usefulness. In addition, irregular and inappropriate uses of these second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
278
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(293 citation statements)
references
References 127 publications
4
278
0
11
Order By: Relevance
“…Such works highlighted the potential of some AGs for treating nonsense mediated human genetic disorders by encoding near-cognate tRNA molecules at premature termination codon positions (5)(6)(7). Other studies have shown that specific AGs can be used as alternative treatments for infections caused by human parasitic protozoa such as trypanosomiasis, giardiasis, amoebiasis and leishmaniasis (8)(9)(10)(11)(12). Nevertheless, despite the great potential use of AGs for additional therapeutic purposes, very little information is available regarding their molecular mechanisms of action in eukaryotes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such works highlighted the potential of some AGs for treating nonsense mediated human genetic disorders by encoding near-cognate tRNA molecules at premature termination codon positions (5)(6)(7). Other studies have shown that specific AGs can be used as alternative treatments for infections caused by human parasitic protozoa such as trypanosomiasis, giardiasis, amoebiasis and leishmaniasis (8)(9)(10)(11)(12). Nevertheless, despite the great potential use of AGs for additional therapeutic purposes, very little information is available regarding their molecular mechanisms of action in eukaryotes.…”
mentioning
confidence: 99%
“…It affects millions of people worldwide, appearing mainly in tropical and subtropical areas (12). The parasite is transmitted by sandflies and, depending on the type of disease, can be fatal if untreated.…”
mentioning
confidence: 99%
“…DHFR is a key enzyme in folate metabolism, linked to the production of thymidine (12). In several species of protozoa, the catalytic activities for the enzymes DHFR and TS reside on a single polypeptide chain, constituting a bifunctional DHFR-TS enzyme (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…The ORF of the DHFR-TS has been amplified, cloned and sequenced; the sequences showed a high degree of conservation, both at nucleotide (96%) and protein (90%) level. The bifunctional enzyme has been thus considered as a potential drug target (12,15). Nevertheless, there are no reports on the bifunctional enzyme on Le.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation